2020
DOI: 10.1038/s41598-019-57131-1
|View full text |Cite
|
Sign up to set email alerts
|

3D-printing process design of lattice compressor impeller based on residual stress and deformation

Abstract: The application of a lattice structure in the lightweight design of compressor impellers can reduce their mass and moment of inertia, hence improving the effective carrying of aircraft and reducing the start and braking moments of the impeller. The feasibility of a processing-lattice compressor impeller is the prerequisite for its application. To control the residual deformation and residual stress effectively, a computer-aided design technique is used to simulate the manufacturing process of a compressor impe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 40 publications
(40 reference statements)
0
11
0
1
Order By: Relevance
“…This combination has also been proposed by Quail et al [39], in the development of an impeller with complex blade profiles, using the FDM technique, verifying how it could represent an excellent alternative to conventional numerical control milling processes which are difficult and expensive for complex geometries. The application of RE techniques for the design of high efficiency impellers, manufactured using SLM, was successfully verified by Jia et al [40] who fabricated a TiAl6V4 lattice structure, to reduce the mass and the moment of inertia, verifying an increase in mechanical and structural performance. Elizondo and Reinert [41] reproduced the spare part of an aircraft's wing holder, made of Inconel 718 alloy, in order to ensure a more efficient, simpler and lightweight design.…”
Section: Introductionmentioning
confidence: 94%
“…This combination has also been proposed by Quail et al [39], in the development of an impeller with complex blade profiles, using the FDM technique, verifying how it could represent an excellent alternative to conventional numerical control milling processes which are difficult and expensive for complex geometries. The application of RE techniques for the design of high efficiency impellers, manufactured using SLM, was successfully verified by Jia et al [40] who fabricated a TiAl6V4 lattice structure, to reduce the mass and the moment of inertia, verifying an increase in mechanical and structural performance. Elizondo and Reinert [41] reproduced the spare part of an aircraft's wing holder, made of Inconel 718 alloy, in order to ensure a more efficient, simpler and lightweight design.…”
Section: Introductionmentioning
confidence: 94%
“…In some research papers, it was observed that the honeycomb structures are characterized by brittle fracture in dynamic tests, which resulted in significantly worse energy-consuming parameters for that kind of structure [ 13 ]. Different material behavior after the L-PBF processing of thin-walled parts has to be taken into account by designers, especially when constructing parts dedicated to military, aircraft, and medical applications [ 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in our previous research 20 , a lattice based on conventional cubic lattice structure and rotating array lattice structure is proposed for the first time. Under the same load condition, the stress and deformation of rotating lattice filling and conventional lattice filling disk models are compared and verified, and the advantages and disadvantages of two lattice filling models are given in this paper.…”
Section: Introductionmentioning
confidence: 99%